“We Begin 300 Meters Behind the Starting Line”: Adaptation of Iranian Students in Hungary in the Post-Sanctions Era - Hosseini-Nezhad, Sara; Safdar, Saba; Nguyen Luu, Lan Anh (Journal of International Students, 2021)
This longitudinal qualitative research investigated the psychosocial adaptation trajectory of Iranian international students in Hungary and the challenges they encountered. Semistructured interviews were conducted between 7-month to 1-year intervals with 20 Iranian students. Inductive content analysis was utilized to analyze the interview transcripts. Three themes identified were visa and banking challenges, the impact of the currency crisis in Iran on mental health, and positive and negative changes in psychological well-being. The results revealed that almost all students’ well-being improved over time, despite facing challenges related to visas, banking, and Iran’s recent economic crisis.